2018
DOI: 10.1007/s00429-018-1647-8
|View full text |Cite
|
Sign up to set email alerts
|

Developmental abnormality contributes to cortex-dependent motor impairments and higher intracortical current requirement in the reeler homozygous mutants

Abstract: The motor deficit of the reeler mutants has largely been considered cerebellum related, and the developmental consequences of the cortex on reeler motor behavior have not been examined. We herein showed that there is a behavioral consequence to reeler mutation in models examined at cortex-dependent bimanual tasks that require forepaw dexterity. Using intracortical microstimulation, we found the forelimb representation in the motor cortex was significantly reduced in the reeler. The reeler cortex required a sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…Other basic neurodevelopmental features, such as cortical [80] and cerebellar neurogenesis, seem to be as well regulated by the glycoprotein. Consequently, the minicolumnar organization of the cerebral neocortex appeared to be deeply affected by Reln deficiency [81] and some physiological counterparts of cortical connectivity, such as trans-synaptic signal propagation, were also impaired [82]. However, the outcome of Reln deficiency on the microcircuitry sustaining the cortical machinery is controversial and, surprisingly, the deep architectonic disorganization that follows the lack of the protein occurs in the absence of dramatic functional anomalies.…”
Section: Lissencephaly 2 A) Humansmentioning
confidence: 99%
“…Other basic neurodevelopmental features, such as cortical [80] and cerebellar neurogenesis, seem to be as well regulated by the glycoprotein. Consequently, the minicolumnar organization of the cerebral neocortex appeared to be deeply affected by Reln deficiency [81] and some physiological counterparts of cortical connectivity, such as trans-synaptic signal propagation, were also impaired [82]. However, the outcome of Reln deficiency on the microcircuitry sustaining the cortical machinery is controversial and, surprisingly, the deep architectonic disorganization that follows the lack of the protein occurs in the absence of dramatic functional anomalies.…”
Section: Lissencephaly 2 A) Humansmentioning
confidence: 99%
“…The training effect was not evident comparing the forelimb area, ipsilateral to the trained forelimb, either in WT (WT trained ipsi vs. WT ipsi p =0.9979), or in HRM (HRM trained ipsi vs. HRM ipsi p = 0.4400). The cortical thresholds used by the ICMS in evoking movements of the skeletal muscles change with cortical structural abnormalities (Nishibe et al, 2018) but not following a brain lesion (Nishibe et al, 2010) or following reach-tograsp training (Kleim et al, 1998). We found that neither Reelin haploinsufficiency nor the reach-to-grasp training affected the cortical stimulation threshold to evoke forelimb movements by ICMS ( Figure 1F n = 8, WT 69.1 ± 7.77 µA, HRM 61.9 ± 7.65 µA, WT trained 73.6 ± 6.67 µA, HRM trained 58.9 ± 3.16 µA; F 3.…”
Section: Resultsmentioning
confidence: 99%
“…The age of the mice used for the patch clamp was 5 weeks (10 WT and 10 HRM mice) and for the rest of all experiments 17-20 weeks (43 WT, 42 HRM, 10 Dab1 cKO, 10 Dab1 control mice). Genotyping was conducted as previously described (Nishibe et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence, the minicolumnar organization of the cerebral neocortex appeared to be deeply affected by Reln deficiency [169] and some physiological counterparts of cortical connectivity, such as the trans-synaptic signal propagation, were also impaired [170].…”
Section: Division Of Cns Region/division Subdivision/nucleus Type(s) mentioning
confidence: 99%